Peran Dosen Pembimbing Lapangan dalam Meningkatkan Efektifitas Program Kampus Mengajar - Fidesrinur Fidesrinur; Abdullah Hakam Shah; Zahrina Amelia (Universitas Al Azhar Indonesia, 2022)
The objective of the research is to study the role of field advisory lecturer (FAL) in encouraging the effectiveness of teaching assistance program (TAP). The research conducted by using descriptive qualitative method with 4 FALs who supervised 36 students throughout TAP batch 1 and batch 2 around Jakarta and Tangerang. The research finding shows that (1) FAL take important roles in TAP to coordinate planning, actuating, reporting with ministry of education, provincial education office, school and university to assure the positive impact for each side, and (2)TAP is one of Ministry of Education, Culture, Research and Technology policies to synergize between school and university to accelerate basic education quality which is need comprehensive policy dealing conversion within curriculum of each department and its program continuity. It suggest that TAP to be socialized each task among parties, considering curriculum each department for credit semester and assuring continuity of the programKeywords – Efektivitas, DPL, Program Kampus Mengajar, MBKM